The myth of urban poor climate adaptation idiosyncrasy. Issue 128 (February 2022) - Cobbinah, Patrick Brandful; Asibey, Michael Osei; Boakye, Angela Achiaa; Addaney, Michael
Abstract: The growing assumption in urban studies literature is that the urban poor remain vulnerable to climate change impacts yet excluded from planning interventions and their formation. However, at present, there is dearth of research examining the adaptation practices by the urban poor in African cities. Focusing on Ghana's capital, Accra, the purpose of this study is fourfold: (i) to explore climate change literacy among the urban poor and local planning institutions; (ii) to examine the urban poor's perceptions on climatic events in Accra; (iii) to analyze autonomous adaptation measures to climate change impacts; and (iv) to assess planned adaptation measures to climate change impacts. This paper uses household surveys, secondary data analysis and agency interviews in two informal communities - Nima and Chorkor - in Accra as case studies. Underpinned by the social exclusion theory, the results show limited climate literacy despite widespread experience of climate change impacts by the urban poor. Most adaptation measures were community driven and autonomous while the limited institutional responses were both planned and autonomous. However, both community and institutional planning responses were ad-hoc, reactionary and unsustainable. The paper recommends consideration of community-based self-organizing adaptation measures into city plans to ensure that autonomous measures are complemented with planned adaptation strategies. In addition to stakeholder participation, collaborations and partnerships in climate change adaptation, pro-poor adaptation measures - both autonomous and planned remain imperative as they can contribute to inclusive and just climate change policy. Highlights: Urban poor remain vulnerable to climate change impacts. They are excluded from climate planning action. Adaptation measures were community driven and autonomous. Institutional responses to climate change are unsustainable. Stakeholder partnerships in pro-poor adaptation required.